New directions in dental anthropology paradigms, methodologies and outcomes - Townsend, Grant; Kanazawa, Eisaku; Takayama, Hiroshi (University of Adelaide Press, 2012)
"This book contains papers arising from a symposium held during a combined meeting of The International Union of Anthropological and Ethnological Sciences (IUAES), The Australian Anthropological Society (AAS) and The Association of Social Anthropologists of Aotearoa New Zealand at the University of Western Australia from July 5-8th, 2011." -- from cover description.